Optimizing Supplier Selection: Leveraging Analytic Hierarchy Process (AHP) in Purchasing Decision Support Systems - Hamizahrul, Fadhilatul Yusuf (International Enterprise Integration Association, 2024)
This research delves into the application and significance of the Analytic Hierarchy Process (AHP) in the domain of purchasing decisions, focusing on the structured methodology's impact on decision-making processes. The study seeks to explore how AHP serves as a robust decision support system, aiding in supplier selection, criteria prioritization, and overall procurement strategies. The research methodology involves a comprehensive analysis of AHP's implementation in the context of purchasing decisions. It encompasses a systematic review of literature, data collection methods including surveys and interviews with stakeholders, and the application of AHP models in evaluating and ranking suppliers based on identified criteria. Key findings underscore the pivotal role of AHP in structuring complex decisions by breaking them down into hierarchical structures. The research highlights AHP's ability to quantify criteria importance, integrate diverse stakeholder preferences, and prioritize suppliers based on overall performance across critical factors such as cost, quality, and delivery time. The outcomes of this study showcase the significant impact of AHP on enhancing decision quality, transparency, and resource optimization in purchasing decisions. The findings emphasize the methodology's adaptability to changing contexts and its role in fostering continuous improvement, aligning choices with organizational objectives, and mitigating risks associated with supplier selection.